A Rare Closed Reduction of Posterolateral Dislocation with Medial Collateral Ligament (MCL) Injury : A Case Report - Affan, Ritzky Pratomo; Adityawardhana, Taufan; Soraya, Fira (Universitas Baiturrahmah, 2022)
Introduction: Irreducible posterolateral dislocation of the knee is a rare condition. Due to limited reports available, it is a common dilemma whether closed reduction should be attempted at all or an open surgery is the only method. “Dimple Sign'' can be found in the presence of injured medial structure, including the medial collateral ligament rupture (MCL), failure to recognize this sign may lead to repeated attempts of close manual reduction where could lead to secondary soft tissue injuries. Case Report : In this study we present a 50 years old male with successful attempt of closed reduction in posterolateral knee dislocation combined with tendon repair for the MCL rupture. Conclusion: This study may add more perspective and be beneficial for similar cases where prompt open surgery is not possible and closed reduction is considered.